2005
DOI: 10.1099/mic.0.28421-0
|View full text |Cite
|
Sign up to set email alerts
|

Production of anti-neurotoxin antibody is enhanced by two subcomponents, HA1 and HA3b, of Clostridium botulinum type B 16S toxin–haemagglutinin

Abstract: Clostridium botulinum type B strain produces two forms of progenitor toxin, 16S and 12S. The 12S toxin is formed by association of a neurotoxin (NTX) and a non-toxic non-haemagglutinin (NTNH), and the 16S toxin is formed by conjugation of the 12S toxin with a haemagglutinin (HA). HA consists of four subcomponents designated HA1, HA2, HA3a and HA3b. When mice were immunized with formalin-detoxified NTX, 12S or 16S, a significantly greater amount of anti-NTX antibody (Ab) was produced in the mice injected with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 26 publications
2
66
0
2
Order By: Relevance
“…The biological and structural roles of the complex proteins are not completely characterized, although it has been proposed that they serve the role of protecting BoNT from harsh conditions, including pH, salt, temperature, and digestive enzymes, and that they assist BoNT translocation across the intestinal epithelial layer (2,6,17). A recent report indicated that the nontoxic proteins serve as adjuvants and contribute to the immunogenicity of BoNT/A (25).…”
mentioning
confidence: 99%
“…The biological and structural roles of the complex proteins are not completely characterized, although it has been proposed that they serve the role of protecting BoNT from harsh conditions, including pH, salt, temperature, and digestive enzymes, and that they assist BoNT translocation across the intestinal epithelial layer (2,6,17). A recent report indicated that the nontoxic proteins serve as adjuvants and contribute to the immunogenicity of BoNT/A (25).…”
mentioning
confidence: 99%
“…These considerations have led the researchers to develop a more practical method of testing by applying the principles of immunodiagnostics such as ELISA. Lee et al (2005), Atassi (2006), and Keller (2008) suggested that if immunodiagnostics need to be developed, it would be better if using antibodies produced from modified C. botulinumintact toxin. They found that "home-made vaccine" from native C. botulinum antigens were more immunogenic and more protective than those of commercial antigens (Keller, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…39 Various factors might affect BONT-A immunogenicity. They include product-related factors, such as manufacturing process and antigenic protein load (accessory proteins have been shown to increase the immunological response to NTX-A [40][41][42] ), as well as treatment-related factors, such as overall toxin dose and prior vaccination or exposure.…”
Section: Rationale Of Treatment Dosage Concentration and Injection mentioning
confidence: 99%